Jovens e associações em Moçambique: motivações e dinâmicas actuais [Youths and associations in Mozambique: motivations and current dynamics] - Biza, Adriano Mateus (Saúde e Sociedade, 2009)
O presente artigo é uma reflexão sobre dinâmicas associativas de jovens no Moçambique pós colonial. O objectivo desta reflexão foi identificar e analisar as motivações de engajamento dos jovens nesses agrupamentos. Baseando-se em aproximações empíricas feitas a duas associações de jovens - Associação Aro Juvenil e Associação Positiva Juvenil - a análise demonstra que dinamica associativa de jovens mete em evidência relações complexas entre identidade, contexto, o privado, o público e o afectivo. Embora haja múltiplas motivações, a adesão dos jovens em associações associa trajectórias e expectativas individualizadas. A nível discursivo, a entrada na vida associativa representa uma forma de legitimação sóciopolítica em resposta a um discurso que considera os jovens passivos e pouco intervenientes na solução dos problemas que lhes afecta em particular e à sociedade no geral. A nível das práticas associativas quotidianas, os jovens reintrepretam e dão outro sentido às motivações do seu engajamento: para lá dos objectivos formais, pretensamente desenvolvimentistas, altruistas e humanitários, o associativismo é uma estratégia de vida e de realização de projectos individuais. Criar uma associação e/ou nela aderir pode significar maiores possibilidades de aceder e controlar recursos e capitais diversificados como emprego/profissão, dinheiro, trabalho, poder, reconhecimento e prestigio, formações entre outros que de outra forma não seria possível. en: This article reflects on youth associations dynamics in Postcolonial Mozambique. The aim is to identify and analyze motivations for young people's involvement in such groups. Based on empirical work with two youth associations - namely "Associação Aro Juvenil" and "Associação Positiva Juvenil" - the assessment finds that youth associations dynamics highlights intricate relationships involving identity, context, private, public and affective milieus. Although there are multiple motivations, young people's adherence to associations is combined with individual life stories and expectations. At the discourse level, entrance to the associative life represents a form of socio-political legitimation in response to other narratives that consider young people very passive and less intervening in finding solutions to their own problems, and society's in general. At the level of day-to-day practices, young people re-interpret and give a different sense to their motivations and commitment: beyond formal objectives - arguably development-oriented, altruistic and humanistic - associations are a life strategy for the accomplishment of individual achievements. To create an association and/or take part in one may imply greater possibilities of accessing and controlling diversified resources and capitals, such as a job/occupation, money, work, power, recognition, prestige, and training, among others, which would be otherwise impossible.
Publisher: Saúde e Sociedade
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; decentralization / descentralização; youth / juventude

Power and Participation in Rural Development: A Case Study from Mozambique - Valderrama, Camilo Eduardo (Institute of Development Studies, University of Sussex, 2009)
This study on power and participation in post-conflict settings analyzes a rural development project in Mandimba District of Northern Mozambique. The purpose is to gain understanding of the dynamics and possibilities of participatory approaches for increasing the influence of previously excluded actors in decision-making processes. The methodology for this study reflects two broad yet intertwined approaches. For the first component, the Mozambique in-depth case study research, I draw on my role as a participant observer as well as other more traditional field research approaches. A variety of qualitative methods were used for the collection of the information, including review of documentary sources, participant observation, key informant and focus group interviews. The initial data collection lasted about eight months in different phases between 1998 and 1999. In Mozambique, but also in subsequent years, my approach drew upon principles of reflective practice, where I learned not only through the study of others, but through reflections on my work as a practitioner in conflict areas being studied. This latter approach was particularly important when triangulating and extending the findings from the Mozambique study to other war-torn settings in which I later worked in Kosovo, Pakistan and Chad and when reviewing documented experiences in participatory processes in Afghanistan and East Timor. A 'power over' and 'actor oriented' approach informed data collection and analysis of the information. The findings show that inclusive participatory approaches may fail if they do not address power. They may sideline power asymmetries and fail to set rules of involvement for actors within the project. In addition, structural and functional factors related to the project frame can enhance or constrain participation. The finding also shows that the inflexibility of the project frame constrains actor engagement in decision-making processes. The theoretical implication of this research calls for an approach to power rooted in the mix of conflict and consensual understanding of power. Practical implications point towards a greater emphasis on 'decision ruling', i.e. setting the 'rules of the game' for decision-making in participatory processes.
Publisher: Falmer : University of Sussex
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mandimba; GP - Niassa; L - english / inglês; citizenship & participation / cidadania e participação; conflict - civil war / conflito - guerra civil; conflict / conflito; power / poder; rural development / desenvolvimento rural

Mozambican Civil Society Within: Evaluation, Challenges, Opportunities and Action - Fundação para o Desenvolvimento da Comunidade (FDC) (Fundação para o Desenvolvimento da Comunidade (FDC), 2007)
This section presents the main results of the CIVICUS Civil Society Index (CSI) research project in Mozambique conducted between March and December 2007. The project was implemented by the Community Development Foundation (FDC) in close collaboration with CIVICUS (World Alliance for citizen participation) and with financial support from the United Nations Development Programme (UNDP), the Aga Kahn Foundation and the European Union. The CSI project is an integrated research effort involving multiple sources, quantitative and qualitative methods and broad participation by actors and stakeholders in evaluating the state of civil society throughout the world. In line with the CIVICUS CSI methodology, the FDC established a National Index Team (NIT) and a National Advisory Group (NAG). The entire implementation process was monitored and supported by the CIVICUS team but totally implemented by the team of national researchers, and advised by NAG. The technical team met, systematised and analyzed information from a variety of sources, both secondary and primary. At different stages of the research the data and results were subject to ample discussion and critical analysis, especially in meetings of the NAG that validated the final score for the 80 indicators that make up the Civil Society Index (CSI). Consultations and data collection covered the whole country and involved two original primary surveys. One was a Community Sample Research (INC07) based on a statistically representative sample of 4015 people. The other was a national survey of 477 civil society organisations (INOSC07) based on a sample taken from the database of INE (2006) that conducted a census of almost 5000 non-profit organisations in 2003. The CSI is an international comparative project that has to date involved some 60 countries using the same CIVICUS methodology. The CSI was conceived with two main objectives: 1) to provide up-to-date and useful knowledge about civil society; 2) to strengthen stakeholder commitment to strengthening and expanding civil society. The final report, on which this Extended Summary is based, has three main chapters. Chapter 3 contains the main analysis and is structured according to the logic of the four CSI subdimensions. This summary describes the main results, including a brief historical overview, the main debate on the civil society concept in the specific case of Mozambique, the results of the four dimensions of the CSI diamond (Structure, Environment, Values and Impact) and finally the strengths and weaknesses of the current state of Mozambican civil society. The data and analysis summarised here are the result of considerable discussion and debate by the NAG and in a three-day national workshop held in Maputo during 4 to 6 December 2007.
Keywords: G - Mozambique / Moçambique; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil

Introduction: Accountability through Participation: Developing Workable Partnership Models in the Health Sector - Cornwall, Andrea; Lucas, Henry; Pasteur, Kath (IDS Bulletin, 2000)
The IDS Participation and Health and Social Change Groups convened a workshop in October 1999 to share experience with the use of participatory approaches in enhancing accountability in the health sector, and to explore some of these challenges. The articles in this bulletin reflect some of the richness of experience on the ground in building effective participation, as well as some of the many issues that arise in moving towards more active citizen engagement with service provision. They bring experience from current and ongoing work to reflect on the links between participation, accountability and improvements in health. The workshop explicitly aimed to reflect on experiences that were moderately successful, in order to identify potential elements that contribute to and impede the success of efforts to build accountability through participation. It is important to emphasise that understanding of the complexities of this approach is at a very early stage. The design of interventions is complex and often highly contextdependent. Rather than attempt to establish any blueprint for future activities, the workshop sought to explore the issues and attempt to advance the debate. In this introduction we draw out some of the principal themes emerging from the articles included here, and from workshop discussions.
Accepted: 2016-02-01T14:49:31Z Publisher: Institute of Development Studies
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; health / saúde